Analisis Anggaran Laba dalam Proses Pengendalian Biaya Operasional pada Koperasi Syariah Indonesia - Ismalinda Wieke W; Ainunnisa Al Rumra; Nabila Intan Azzah; Suryo Budi Santoso (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
AbstracktManagement control is a system that controls all activities that occur within a company in order to determine the right strategy and implement it to achieve company goals. While the cooperative's profit budget is the income that has been reduced by costs. The higher the income, the higher the profit. The purpose of this case study is to analyze the success of the profit budget in controlling operational costs that can be carried out by sharia cooperative management to increase profits. This study uses a qualitative descriptive method with a literature study method. he results of this study are to show that the profit budget is interconnected with the process of controlling operational costs. So if the budgeted profit is high but you don't control expenses, the profit will be low.Â Keywords: Profit Budget, Management Control, Cost Operasional